Co-circulation of dengue virus serotypes 1 and 3 in the Fatick region of senegal 2018 - Diagne, Cheikh Tidiane; Dieng, Idrissa; Faye, Oumar; Fall, Cheikh; Barry, Mamadou Aliou; Diarra, Maryam; Ndiaye, Oumar; Dior Ndione, Marie Henriette; Ndiaye, Mamadou; Diop, Boly; Bousso, Abdoulaye; Sall, Abiboulaye; et al. (Frontiers in Virology, 2023)
On 10th September 2018, the Syndromic Sentinel Surveillance network that monitors febrile illnesses in all 14 regions of Senegal detected a peak of fever in the Fatick region. On 13 September 2018, 10 samples were sent to the WHO Collaborating Centre for Arboviruses and Viral Haemorrhagic Fevers at the Institut Pasteur de Dakar (IPD). Laboratory investigations revealed an epidemic of dengue 1 genotype V and dengue 3 genotype III. Fatick neighbors the Holy City of Touba where 3.5 million people from all over the word gather every year for the Grand Magal pilgrimage. This article discusses the impact of mass gatherings and their role in the recent introduction of dengue serotypes in Senegal. Dengue is now endemic in Senegal and across many countries in Africa, highlighting the need for early detection, control measures and prevention of severe dengue cases in highly connected urban settings.